Simulation of Natural Gas Transmission Pipeline Network System Performance - Abraham Debebe , Abraham Debebe (David Publishing Company, 2009)
Simulation has proven to be an effective tool for analyzing pipeline network systems (PNS) in order to determine the design and operational variables which are essential for evaluating the performance of the system. This paper discusses the use of simulation for performance analysis of transmission PNS. A simulation model was developed for determining flow and pressure variables for different configuration of PNS. The mathematical formulation for the simulation model was derived based on the principles of energy conservation, mass balance, and compressor characteristics. For the determination of the pressure and flow variables, solution procedure was developed based on iterative Newton Raphson scheme and implemented using visual C++6. Evaluations of the simulation model with the existing pipeline network system showed that the model enabled to determine the operational variables with less than ten iterations. The performances of the compressor working in the pipeline network system which includes energy consumption, compression ratio and discharge pressure were evaluated to meet pressure requirements ranging from 4000-5000kPa at various speed. Results of the analyses from the simulation indicated that the model could be used for performance analysis to assist decisions regarding the design and optimal operations of transmission PNS.